BEYOND THE PROMISES OF TECHNOLOGY: A REVIEW OF THE DISCOURSES AND ACTORS WHO MAKE DRIP IRRIGATION†. (14th March 2014) - Venot, Jean‐Philippe; Zwarteveen, Margreet; Kuper, Marcel; Boesveld, Harm; Bossenbroek, Lisa; Kooij, Saskia Van Der; Wanvoeke, Jonas; Benouniche, Maya; Errahj, Mostapha; Fraiture, Charlotte De; Verma, Shilp; Tyagi, Avinash C.; et al.
ABSTRACT Drip irrigation has long been promoted as a promising way to meet today's world water, food and poverty challenges. In most scientific and policy documents, drip irrigation is framed as a technological innovation with definitive intrinsic characteristics—that of efficiency, productivity and modernity. Based on evidence from North and West Africa as well as South Asia, we show that there are multiple actors involved in shaping this imagery, the legitimacy of which largely stems from an engineering perspective that treats technology and potential as 'truths' that exist independently of the context of use. Rather than ascribing the advent of drip irrigation as a successful technology to intrinsic technical features, this paper proposes to see it as grounded in the ability drip irrigation has to lend itself to multiple contexts and discourses that articulate desirable futures. We thus adopt a view of technology whereby the 'real' (i.e. the drip irrigation hardware) acquires its characteristics only through, and within, the network of institutions, discourses and practices that enact it. Such a perspective sheds light on the iterative alignments that take place between hardware and context and treat these as inherent features, rather than externalities, of the innovation process. Copyright © 2014 John Wiley & Sons, Ltd.